SOCIALIZATION AND IDENTITY FORMATION: A DEVELOPMENTAL PERSPECTIVE IN THE DIGITAL AGE - Tan, Ethan; Tan, Marcus; Suzuki, Ren (Yayasan Adra Karima Hubbi, 2026)
In the digital age, socialization processes and identity formation have become increasingly intertwined with digital platforms and technologies. The digital environment presents new opportunities and challenges in the development of self-concept and social interactions, which have significant implications for various developmental stages. However, there is limited research exploring how digital spaces influence identity formation, especially from a developmental perspective. This study aims to investigate how digital socialization processes impact identity formation across different age groups and developmental stages, focusing on the interaction between online and offline environments. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with individuals from diverse age groups. The survey explored the frequency and nature of digital interactions, while the interviews provided in-depth insights into personal experiences with identity formation in digital spaces. The findings reveal that digital platforms significantly influence self-concept and identity development, with younger individuals more likely to engage in self-exploration through digital spaces. Digital socialization plays a critical role in identity formation, particularly in adolescence and early adulthood. Future research should focus on how digital interactions shape identity development over time and across different cultural contexts.